Pengaruh Pelatihan Kerja terhadap Prestasi Kerja Karyawan pada BPJS Ketenagakerjaan Kantor Cabang Jambi - Ikaputri, Tasya Dian; Andriana, Isni; Farla, Wita; Santati, Parama (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine how the effect of training on employee of BPJS Ketenagakerjaan in Jambi City. The population in this study amounted to 31 people with the sampling method using the saturated sample method. The data used in this study used primary data with data collection techniques through questionnaires. The data analysis technique used is simple linear regression analysis. The results of this study indicate that training has a positive and significant effect on employee work achievement at BPJS Ketenagakerjaan in Jambi City. Keywords: training, employee work achievement